2009
DOI: 10.1038/oby.2009.49
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Gene Expression in Morbidly Obese Women: Implications for Disease Susceptibility

Abstract: The objective of this study was to determine the molecular bases of disordered hepatic function and disease susceptibility in obesity. We compared global gene expression in liver biopsies from morbidly obese (MO) women undergoing gastric bypass (GBP) surgery with that of women undergoing ventral hernia repair who had experienced massive weight loss (MWL) following prior GBP. Metabolic and hormonal profiles were examined in MO vs. MWL groups. Additionally, we analyzed individual profiles of hepatic gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 57 publications
6
33
0
Order By: Relevance
“…Recent reports revealed that the increased in the synthesis of fatty acids enhances HCV replication (Kapadia and Chisari, 2005). Our results showed upregulation of ELOVL2 gene and is in agreement with Elam et al (2009) who reported ELOVL2 overexpression in morbidly obese women.…”
Section: Discussionsupporting
confidence: 82%
“…Recent reports revealed that the increased in the synthesis of fatty acids enhances HCV replication (Kapadia and Chisari, 2005). Our results showed upregulation of ELOVL2 gene and is in agreement with Elam et al (2009) who reported ELOVL2 overexpression in morbidly obese women.…”
Section: Discussionsupporting
confidence: 82%
“…This draws support from a previous report that observed an elevation in the expression of REDD1 from liver tissue of morbidly obese humans (22). Glucocorticoids are elevated in the obese under both fasted and fed conditions (3,49,80).…”
Section: Discussionsupporting
confidence: 76%
“…oxygen species accumulation is in general associated with cellular insulin resistance (29), increased REDD1 expression in response to insulin could participate to the development of insulin resistance. This latter hypothesis is reinforced by the observation that expression of REDD1 is significantly higher in liver of morbidly obese patients (30).…”
Section: Discussionsupporting
confidence: 55%